Penerapan Model Problem Based Learning Berbantuan Media Wordwall Untuk Meningkatkan Hasil Belajar Pendidikan Pancasila di Kelas III SDN Sawah Besar 01 - Idza Rosiana; Khusnul Fajriyah; Joko Sulianto; Theresia Sawitri (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This research discusses how to improve student learning outcomes in Pancasila Education subjects. Students still have difficulties in understanding ethnic diversity material in Indonesia. This research was conducted using the Problem Based Learning learning model in grade III of SDN Sawah Besar 01 Semester 2 Year 2024/2025. The PTL model used is a spiral model from Kemmis, S and Mc Taggart, R uses two cycles where each cycle is independent of four stages, namely (1) Action Planning, (2) Action Implementation, (3) Observation, and (4) Reflection. The subject of this study were grade III students of SDN Sawah Besar 01, Gayamsari District, Semarang City, as many as 29 children consisting of 15 male students and 14 female students. The data analysis method is qualitative and quantitative. The conclusion of this study using the PBL model with Wordwall media resulted in an increase in learning outcomes. The results of improving learning model can be seen from the percentage of completeness in pre-cycle conditions of 17,24% cycle I increased to 41,38% and in cycle II increased to 79,31% with KKTP 75.